INTRARETINAL FIBROSIS IN MACULAR TELANGIECTASIA TYPE-2: CLINICAL AND MULTIMODAL IMAGING FEATURES - Kiran Chandran; Anantharaman Giridhar; Mahesh Gopalakrishnan; Sobha Sivaprasad (RETINAL Cases & Brief Reports, 2026)
Purpose: To explore the clinical and multimodal imaging characteristics of intraretinal fibrosis (IRFib) in macular telangiectasia type-2 (MacTel). Methods: Macular telangiectasia type-2 eyes with IRFib that had multimodal imaging with color fundus photography, multicolor, blue reflectance, spectral-domain optical coherence tomography, optical coherence tomography angiography, and fluorescein angiography. Results: Seven eyes of six patients were included. Clinically, all cases had grayish-white fibrosis at macula, with retinal vessel tortuosity in two cases best characterized on multicolor. Two eyes each belonged to Gass and Blodi stages 3 and 4, three eyes were stage 5 MacTel. The mean lesion area at presentation was 1.36 mm 2 ± 0.81 mm 2 (range 0.56–2.99 mm 2 ). The defining optical coherence tomography finding for IRFib was hyper-reflective distortion intraretinally (involving different layers). Other accompanying findings in decreasing order were collapse sign (seven eyes); epiretinal membrane (six eyes); pigment clumping and migration (five eyes); serrated internal limiting membrane and outer-retinal hyper-reflectivity (four eyes); and lamellar macular hole (one eye). On optical coherence tomography angiography, IRFib was associated with right-angled vessels, vascular invasion and distortion of foveal avascular zone, and vessel dilatation and tortuosity in superficial vascular complex; telangiectasia, foveal avascular zone distortion and invasion, vessel drag, capillary looping, and abnormal vascular structures in deep capillary plexus; and nodular tuft or twig-like hyper-reflective vascular lesions in outer-retina choriocapillaris slab. Conclusion: The incidence of IRFib on multicolor in our MacTel cohort was 1.75% with characteristic findings on optical coherence tomography and optical coherence tomography angiography. They are associated with advanced MacTel and probably implicate Müller cell dysfunction, activated glial cells, and vascular changes during the disease process.